Future Red Pepper Picker - Othman, Khairulnizam; Amirul Hakim,; Fitri Ikhwan,; M. Ilmi, (Multidisciplinary Applied Research and Innovation, 2023)
Mechanical Engineering is an engineering field what was long a in the history of mankind. Thus, many of the efforts to study and come up with something new methods or products associated with this field because it guarantees high returns and very important for the development of the present and the future. This study was conducted to produce a pepper/chilli picker to shorten the harvest time by using the appropriate components. Studies on problems often faced by farmers or suppliers indicate a solution framework needs to be developed. The development of this project is important to make it easier for farmers or suppliers to harvest crops quickly by meeting the period of pepper/chilli days which are very suitable to be harvested as well as get good freshness to be sent to wholesalers. To make it easier, we designed a tool to form a pepper/chilli picker without having to use a machine to do the harvesting process. Overall, this project will facilitate and replace the daily routine work of farmers or suppliers who do the work of picking very much pepper/chilli on the tree.